The Protective Function of Coastal Habitats in Mitigating Erosive Vulnerability: A Case Study on Sandy Beaches of the Equatorial Atlantic, Northeastern Brazil - Carvalho, Gabriel Dalla Rosa; Amaro, Venerando Eustáquio; Pinheiro, Lívian Rafaely de Santana Gomes; Zamboni, Nadia Selene (Revista Brasileira de Geomorfologia, 2025)
Coastal environments are subject to intense pressure from both natural and anthropogenic factors, often culminating in landscape alterations such as sandy beach erosion. On the northern coast of Rio Grande do Norte (RN), rapid urban and tourist expansion has intensified these processes. This study assesses coastal vulnerability to erosion along sandy beaches segments in the municipality of São Miguel do Gostoso (RN), considering the protective function of natural habitats, specifically dunes, vegetation, and beach stretches. The methodology is based on remote sensing and geoprocessing data, involving the examination of historical shoreline variation from 1986 to 2023, as the application of the Coastal Vulnerability Index via the Integrated Valuation of Environmental Services and Tradeoffs (InVEST) model. The results indicate an increase in mean shoreline mobility during the more recent period (2014–2023), with intensified minimum and maximum rates of variation, particularly in areas subjected to greater anthropogenic influence, where the average erosion rate reaches -14.55 m/year. It was further found that dunes and sandy beaches function as effective natural barriers, thereby reducing erosion. The conservation of these habitats is essential for the environmental balance of the coastal zone, especially in the face of increasing urban expansion in the municipality